Simplification with Boosted Protease Inhibitor-Based ART Versus Maintenance of Conventional ART: Results from a Five-Year Controlled Cohort - Mateus Swarovsky Helfer; Guilherme Carvalho Serena; Tarsila Vieceli; Eduardo Sprinz (Viruses)
Dolutegravir-based antiretroviral therapy (ART) simplification is increasingly common, although some patients cannot take this drug due to intolerance or drug resistance. Boosted-protease inhibitors (bPI) might be an option in this scenario. Nevertheless, long-term outcomes have not been studied yet. A controlled cohort study comparing 5-year outcomes of ART simplification bPI-based regimens (without integrase strand transfer inhibitor—INSTI) versus ART maintenance was conducted in a Brazilian referral center. Viral suppression rates and mortality after 5 years were the primary outcomes of the study. Eighty individuals were included in each group; 47.5% were women, and the mean age was 56 years. The five-year survival rate was 88.8% in the simplified group and 87.5% in the maintenance arm (log-rank = 0.41). Viral suppression rate was 78.8% and 70.0%, respectively (p = 0.28). Individuals presented less renal function decline (−5 vs. −10 mL/min/1.73 m2; p < 0.05) in the simplified arm. No difference was observed in metabolic parameters. Based on our findings, ART simplification without INSTI has shown efficacy and safety comparable to maintenance of triple therapy even in the long term, and could be an option in these situations, which might be even more important in settings with limited options.